COMPARATIVE ANALYSIS OF TRANSPORT LEGISLATION IN UZBEKISTAN AND DEVELOPED COUNTRIES - Erkinov Shaxzodbek (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This article provides a comparative analysis of the transport legislation of the Republic of Uzbekistan against Germany, Singapore, and Japan. The analysis covers four key areas: BRT lane protection, parking regulation, pedestrian safety, and driver demerit point systems. Field observation results conducted in 2024 on Abdurauf Fitrat Street near the Old City farmers' market in Andijan serve as the practical basis for comparison. The study shows that Uzbekistan is approaching international standards through the 2025 introduction of the E-point electronic demerit system, but remains 3–50 times behind developed countries in terms of fine amounts and automated enforcement.